ASSESSMENT OF EARLY MARRIAGE AND DOMESTIC VIOLENCE PREVENTION MEASURES CASE STUDY IN GARUT REGENCY, WEST JAVA - Suriadi, Jadi Suriadi (University of Darussalam Gontor Press, 2024)
This study investigates the effectiveness of socialization and education initiatives aimed at addressing early marriage (EM) and domestic violence (DV) prevention in Garut Regency. Utilizing the Maslahah index as a framework, the research delves into various aspects including socialization efforts, perception, participation, and acceptability scores, structured and non-structured data acquisition, evidence-based findings, and recommendations. The socialization and education programs implemented successfully raised awareness and fostered dialogue on EM and DV prevention, evidenced by significant community engagement. The configuration of the Perception, Participation, and Acceptability (PPA) scoring system facilitated a comprehensive understanding of community attitudes, backed by statistical analysis and social interpretation. Moreover, non-structured data acquisition enriched the research with qualitative insights, enhancing the credibility of evidence-based data. Quantitative figures revealed positive assessments of Maslahah, indicating substantial societal benefit from prevention efforts. Furthermore, discussions on leveraging digital education, improving acceptability scores, utilizing AI for data processing, and employing the Wellbeing Methodology (WM) highlight opportunities for enhancing research methodologies and addressing complex societal issues effectively. This study provides valuable insights and recommendations for policymakers, practitioners, and stakeholders to strengthen EM and DV prevention efforts in Garut Regency, underscoring the importance of evidence-based approaches and cross-sectoral collaboration in promoting societal well-being